Πρακτική άσκηση στο μεταφραστικό γραφείο metaphrastic: Έκθεση αποτίμησης - (:unkn) unknown (My University, 2023)
Η παρούσα εργασία αποτελεί έκθεση αποτίμησης της πρακτικής άσκησης που πραγματοποιήθηκε στο πλαίσιο του Προγράμματος Μεταπτυχιακών Σπουδών «Επιστήμη της Μετάφρασης» του Τμήματος Ξένων Γλωσσών, Μετάφρασης και Διερμηνείας. Βασικές παράμετροι ανάπτυξης του θέματος αποτελούν με σειρά προτεραιότητας: ο συνεργαζόμενος φορέας, η ασκούμενη, οι μεταφραστικές και γενικότερες προκλήσεις, οι παρατηρήσεις για την αντιμετώπιση των προκλήσεων και, τέλος, τα επιλογικά σχόλια. Την έκθεση πλαισιώνει παράρτημα με δείγμα παραδοτέων από την άσκηση.

The present essay serves as an evaluation report of the practical training undertaken as part of the Postgraduate Program “Science of Translation” of the Department of Foreign Languages, Translation & Interpreting. The essay is built around five broad areas in the following order: the organization offering real-life translation projects, the student’s involvement in the translation life cycle, the challenges that arose during the training coupled with a discussion on the chosen solutions and finally the concluding remarks. An annex, with a sample of project deliverables from the training, is also included.
Practical Training at Metaphrastic Boutique Language Services: An Evaluation Report
Keywords: πρακτική άσκηση, ιατρική μετάφραση, μετάφραση παιδικής λογοτεχνίας, κυριωνύμια, αρκτικόλεξα, ομοιοκαταληξία; practical training, medical translation, children's literature and translation, proper name, acronym, initialism, rhyme